2010
DOI: 10.2147/cpaa.s6525
|View full text |Cite
|
Sign up to set email alerts
|

Somatotropin in the treatment of growth hormone deficiency and Turner syndrome in pediatric patients: a review

Abstract: Growth hormone (GH), also known as somatotropin, is a peptide hormone that is synthesized and secreted by the somatotrophs of the anterior pituitary gland. The main action of GH is to stimulate linear growth in children; however, it also fosters a healthy body composition by increasing muscle and reducing fat mass, maintains normal blood glucose levels, and promotes a favorable lipid profile. This article provides an overview of the normal pathophysiology of GH production and action. We discuss the history of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Growth hormone (GH) therapy has become the standard of care for girls with TS and should be considered as soon as decreased linear growth velocity is apparent (4,9). Several studies have shown that GH therapy accelerates growth velocity and improves final adult stature.…”
Section: Growth Hormone In Tsmentioning
confidence: 99%
“…Growth hormone (GH) therapy has become the standard of care for girls with TS and should be considered as soon as decreased linear growth velocity is apparent (4,9). Several studies have shown that GH therapy accelerates growth velocity and improves final adult stature.…”
Section: Growth Hormone In Tsmentioning
confidence: 99%
“… 6 9 Recombinant human growth hormone (rhGH) treatment still remains the only established active treatment option to effectively correct growth failure and increase stature. 10 The primary objective of the treatment during childhood and adolescence is to accelerate and normalize height velocity and linear growth, returning the child to the normal growth curve, in order to attain a “normal” or near-normal final adult height within the genetic mid-parental height potential. 7 , 11 13 RhGH treatment is administered via a daily subcutaneous injection, given by the parent/caregiver or self-administered within the home environment.…”
Section: Introductionmentioning
confidence: 99%
“…This gland is responsible for the secretion of somatotropin, the main effect of which is the stimulation of growth during childhood and the maintenance of a healthy body by increasing the volume of muscles and the consumption of fat mass. Additionally, somatotropin is responsible for keeping the concentration of glucose in blood stable [ 12 ].…”
Section: Fda -Approved and -Withdrawn Drugsmentioning
confidence: 99%